The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1021/ja050732x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Stable and Cell-type Selective Analogues of Cyclic ADP−Ribose, a Ca2+-Mobilizing Second Messenger. Structure−Activity Relationship of the N1-Ribose Moiety1

Abstract: We previously developed cyclic ADP-carbocyclic ribose (cADPcR, 2) as a stable mimic of cyclic ADP-ribose (cADPR, 1), a Ca(2+)-mobilizing second messenger. A series of the N1-ribose modified cADPcR analogues, designed as novel stable mimics of cADPR, which were the 2"-deoxy analogue 3, the 3"-deoxy analogue 4, the 3"-deoxy-2"-O-(methoxymethyl) analogue 5, the 3"-O-methyl analogue 6, the 2",3"-dideoxy analogue 7, and the 2",3"-dideoxydidehydro analogue 8, were successfully synthesized using the key intramolecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 46 publications
3
47
0
Order By: Relevance
“…However, to our surprise, it was inactive in T cells, whereas natural cADPR effectively mobilizes Ca 2+ in both neuronal cells and T cells. 34) These results confirmed that the target proteins and/or the mechanism of action of cADPR in sea urchin eggs, T cells, and neuronal cells are different, 35) as suggested by previous biological studies. [36][37][38][39][40][41][42] …”
Section: Cadpcr As a Stable Analogue Of Cadprsupporting
confidence: 84%
“…However, to our surprise, it was inactive in T cells, whereas natural cADPR effectively mobilizes Ca 2+ in both neuronal cells and T cells. 34) These results confirmed that the target proteins and/or the mechanism of action of cADPR in sea urchin eggs, T cells, and neuronal cells are different, 35) as suggested by previous biological studies. [36][37][38][39][40][41][42] …”
Section: Cadpcr As a Stable Analogue Of Cadprsupporting
confidence: 84%
“…This paper constitutes part 235 of Nucleosides and Nucleotides [for part 234 in this series, see (36)]. This work was supported in part by Grant-in-Aid for Scientific Research from the Japan Society for Promotion of Science (No.…”
mentioning
confidence: 99%
“…Each of these methods for measuring Ca 2+ release evoked by cADPR (or cADPR analogs) is characterized by specific advantages and weaknesses (Guse et al 1995(Guse et al , 1997(Guse et al , 1999Kunerth et al 2004;Kudoh et al 2005;Xu et al 2006;Steen et al 2007;Kirchberger et al 2009). In the technique using permeabilized cells, 15 × 10 6 cells are present in the cuvette and so the measured response to cADPR is based on a significant cell number.…”
Section: Discussionmentioning
confidence: 99%